2021
DOI: 10.1186/s12931-021-01683-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single-inhaler extrafine triple therapy versus inhaled corticosteroid plus long-acting beta2 agonist in eastern Asian patients with COPD: the TRIVERSYTI randomised controlled trial

Abstract: Background A single-inhaler extrafine triple combination of beclometasone dipropionate (BDP), formoterol fumarate (FF) and glycopyrronium (G) has been developed for maintenance therapy of chronic obstructive pulmonary disease (COPD). This study evaluated the efficacy and safety of BDP/FF/G in patients in three eastern Asian areas: China, Republic of Korea and Taiwan. Methods TRIVERSYTI was a double-blind, randomised, active-controlled, parallel-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The distribution of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades was as follows: grades 3–4, 40,917 (37.9%) patients; grades 2–4, 39,403 (36.5%) patients; and grades 2–3, 27,536 (25.5%) patients. HD-ICS was used in five RCTs 18 22 , MD-ICS in 15 RCTs 17 , 23 – 34 , and LD-ICS in 10 RCTs 17 , 23 , 24 , 35 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades was as follows: grades 3–4, 40,917 (37.9%) patients; grades 2–4, 39,403 (36.5%) patients; and grades 2–3, 27,536 (25.5%) patients. HD-ICS was used in five RCTs 18 22 , MD-ICS in 15 RCTs 17 , 23 – 34 , and LD-ICS in 10 RCTs 17 , 23 , 24 , 35 39 .…”
Section: Resultsmentioning
confidence: 99%
“…In population-based studies the proportion of current-smoker COPD patients ranged from 34% in Spain to almost 48% in China, with an average of 35.6% [25][26][27][28], whereas in observational studies the proportion ranged from 30% (Daxas in COPD Therapy (DINO) study) to 43.4% (COPDGene cohort) [29][30][31][32][33]. On the other hand, an analysis of individuals with COPD enrolled in some COPD pharmacological clinical trials showed that the proportion of current smokers ranged between 20% and 48%, with an average of 38% [34][35][36][37][38][39][40][41][42][43].…”
Section: Epidemiological Aspects Of Smoking In Copdmentioning
confidence: 99%
“…Pharmacologic management of COPD aims for the reduction of the current symptoms and future exacerbation risks [3]. Treatment of the disease is conducted with inhaled bronchodilators, corticosteroids [4], or long-acting beta-agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of the disease is conducted with inhaled bronchodilators, corticosteroids [4], or long-acting beta-agonists. If the patients have severe symptoms or intense exacerbations, combination therapy has been recommended because it lowers the incidence of exacerbations [3,5]. Budesonide (BUD) belongs to a class of drugs known as corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation